Performance of hypothesis tests for Gompertz distribution with right and interval censored data - Tanusha Nagaraju,; Jayanthi Arasan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study compared the performance of two hypothesis tests for the parameters of the Gompertz distribution in the presence of a covariate, right and interval censored data. Firstly, the performance of maximum likelihood estimation (with and without midpoint imputation) was assessed for this model at various censoring proportion (